First stereospecific total synthesis of (−)-affinisine oxindole as well as facile entry into the C(7)-diastereomeric chitosenine stereochemistry. Issue 23 (3rd June 2015) - Fonseca, German O.; Wang, Zhi-Jian; Namjoshi, Ojas A.; Deschamps, Jeffrey R.; Cook, James M.
Graphical abstract: The first synthesis of (−)-affinisine oxindole was completed in an enantiospecific fashion from commercially availabled -(+)-tryptophan in 10% overall yield. The asymmetric Pictet–Spengler reaction, diastereospecific oxidative-rearrangement of a tetrahydro-β-carboline, and stereospecific enolate-mediated palladium-catalyzed cross coupling process were key steps in the sequence. This represents the first example of a total synthesis via stereospecific entry into either the alstonisine related or epimeric chitosenine related oxindole stereochemistry depending on the presence or absence of an N b -benzyl protecting group. Abstract: The first synthesis of (−)-affinisine oxindole was completed in an enantiospecific fashion from commercially availabled -(+)-tryptophan in 10% overall yield. The asymmetric Pictet–Spengler reaction, diastereospecific oxidative-rearrangement of a tetrahydro-β-carboline, and stereospecific enolate-mediated palladium-catalyzed cross coupling process were key steps in the sequence. This represents the first example of a total synthesis via stereospecific entry into either the alstonisine related or epimeric chitosenine related oxindole stereochemistry depending on the presence or absence of an N b -benzyl protecting group.